Determinants of the adoption of Islamic Finance by Cameroonian SMEs: Case study from a psycho-sociological characteristics of managers - Jérôme Gonne; Yaouba Mohamadou (The Journal of Entrepreneurial Finance (JEF), 2022)
Small and Medium-Sized Enterprises (SMEs) today form the backbone of the African economy in general and Cameroon in particular. However, Cameroonian SMEs encounter many difficulties, one of the most important is the access to so-called conventional financing. Faced with this situation, some of them will seek alternative means such as Islamic finance. Despite its development over the past two decades, Islamic finance is struggling to find a place in the financial decisions of Cameroonian SMEs' Managers. This study aims at highlighting the psycho-sociological characteristics of policymakers in directing their decision towards the Islamic finance product. Data collected from a sample of 57 Cameroonian SMEs, reveals that the degree of adherence to the sharia precepts, the subjective norms, and the perceived relative advantage influence the decision to adopt Islamic finance. These results enrich the literature on SMEs financing and provide financial institutions with tools to lift up this financing circuit.
Keywords: 650; Islamic finance; SMEs; Cameroon; manager's characteristics